Writing Beloveds Humanist Petrarchism and the Politics of Gender - Feng, Aileen A. (Toronto Italian Studies, 2016)
Writing Beloveds considers the way in which a poetic convention, the 'beloved' to whom Renaissance amatory poetry was addressed, becomes influential political rhetoric, an instrument that both men and women used to shape and justify their claims to power.